King : the social archaeology of a late Mississippian town in northwestern Georgia - Hally, David J. (University of Alabama Press, 2008)
At the time of Spanish contact in AD 1540, the Mississippian inhabitants in north-western Georgia and adjacent portions of Alabama and Tennessee were organized into a number of chiefdoms distributed along the Coosa and Tennessee rivers and their major tributaries. This book is about one such town, known to archaeologists as the King site.